1997
DOI: 10.1046/j.1471-4159.1997.69030889.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 and Its Role in Brain Tissue

Abstract: Phospholipase A2 (PLA2) is the name for the class of lipolytic enzymes that hydrolyze the acyl group from the sn-2 position of glycerophospholipids, generating free fatty acids and lysophospholipids. The products of the PLA2-catalyzed reaction can potentially act as second messengers themselves, or be further metabolized to eicosanoids, platelet-activating factor, and lysophosphatidic acid. All of these are recognized as bioactive lipids that can potentially alter many ongoing cellular processes. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
202
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(211 citation statements)
references
References 64 publications
5
202
0
3
Order By: Relevance
“…16 Upon reperfusion, the released PUFA can be used as substrates for oxygenation reactions catalyzed by several groups of cytosolic enzymes-COX, LOX, different cytochrome P450 isoforms, and peroxidases. 16 The major sources of phospholipids for Ca 2+ -dependent PLA 2 -mediated FA hydrolysis are PE, PC, and PS of plasma and intracellular membranes with simultaneous accumulation of lysoPE, lysoPC, and lysoPS, respectively. 16 Previous work in focal cerebral ischemia showed that activation of Ca 2 + -dependent PLA 2 generates oxygenated AA and DHA derivatives in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Upon reperfusion, the released PUFA can be used as substrates for oxygenation reactions catalyzed by several groups of cytosolic enzymes-COX, LOX, different cytochrome P450 isoforms, and peroxidases. 16 The major sources of phospholipids for Ca 2+ -dependent PLA 2 -mediated FA hydrolysis are PE, PC, and PS of plasma and intracellular membranes with simultaneous accumulation of lysoPE, lysoPC, and lysoPS, respectively. 16 Previous work in focal cerebral ischemia showed that activation of Ca 2 + -dependent PLA 2 generates oxygenated AA and DHA derivatives in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of phospholipids, monolysophospholipids, and CL oxidation was performed by liquid chromatography-mass spectrometry (LC-MS) utilizing Dionex HPLC system coupled to a LXQTM ion trap MS or to a hybrid quadrupole-orbitrap mass spectrometer, Q-Exactive (ThermoFisher, Inc., San Jose, CA, USA) as described previously. [14][15][16] For additional detailed analysis of CL and monolyso-CL, normal phase column Luna 3 μm Silica (2) 100 Å column (Phenomenex, Torrance, CA, USA) and gradient solvent A (hexane/propanol/water, 47:57:1, v/v) and solvent B (hexane/propanol/ water, 47:57:10, v/v) each containing 5 mmol/L ammonium acetate and 0.01% formic acid was used. The column was eluted at a flow rate of 0.05 mL/min as follows; 0 to 3 minutes, linear gradient,10% to 37% solvent B; 3 to 12.5 minutes, isocratic at 37% solvent B; 12.5 to 20 minutes, linear gradient, 37% to 100% solvent B; 20 to 45 minutes, isocratic at 100% solvent B; 45 to 60 minutes, isocratic at 10% solvent B.…”
Section: Cardiac Arrest Modelmentioning
confidence: 99%
“…5,6,11,103 An increasing body of evidence suggests that AA is altered in schizophrenia in a causative manner:…”
Section: Discussionmentioning
confidence: 99%
“…45 Indeed, LOX metabolites were found to be synthesized in both neurons and glial cells. 21,[46][47][48] Some of them, such as 5-and 12-hydroxyeicosatetraenoic acids, have been reported to exert various actions on neurons, including modulation of Na-K ATPase activity, 49 neurotransmitter release 50 or alteration of membrane potential. 51,52 LOXs also act as regulators of cell proliferation and death, and have been implied in the mediation of apoptosis induced by various physical or chemical agents such as UV light, oxidative stress or receptor ligands 25,26 In contrast, only a small number of studies investigated the involvement of LOXs in the various signaling pathways leading to neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%